Impaired Thyroid Hormone Sensitivity is Associated with Increased Risk of Liver Fibrosis in Euthyroid Population: A Cross-Sectional Analysis of NHANES - Yao, Xingyu; Xiao, Kaiwen; Oo, Hein Ko (Hormone and Metabolic Research, 2025)
The interplay between liver fibrosis and thyroid function remains incompletely understood, particularly regarding thyroid hormone sensitivity. Thus, this study aims to explore the relationship between liver fibrosis and thyroid hormone sensitivity in euthyroid US individuals. This study involved 4,678 euthyroid participants from the National Health and Nutrition Examination Survey 2007–2012. Key clinical parameters were extracted, including thyroid-stimulating hormone, free and total thyroxine, and liver function-related data. Thyroid hormone sensitivity was assessed by three indices: the Thyroid Function Quotient Index, Thyroid-Stimulating Hormone Index, and Thyrotrophic Thyroxine Resistance Index. Multiple regression analyses and machine learning models were performed to evaluate the relationships between liver fibrosis and thyroid sensitivity indices. Participants with advanced liver fibrosis indicated by fibrosis index 4 (FIB-4) demonstrated significantly impaired thyroid hormone sensitivity indicated by Thyroid Function Quotient Index, Thyrotrophic Thyroxine Resistance Index, and Thyroid-Stimulating Hormone Index. Then, the logistic regression and restricted cubic spline analysis indicated that Thyroid Function Quotient Index, Thyrotrophic Thyroxine Resistance Index, and Thyroid-Stimulating Hormone Index were risk factors for liver fibrosis (odds ratio>1, p<0.05). Furthermore, we developed machine learning models using random forest and Boruta’s algorithm identifying thyroid hormone sensitivity indices, Thyroid-Stimulating Hormone Index, Thyrotrophic Thyroxine Resistance Index, and Thyroid Function Quotient Index as key predictors for liver fibrosis. Mediation analysis indicates that uric acid is a weak mediator between thyroid hormone sensitivity and liver fibrosis. This study reveals that impaired thyroid hormone sensitivity is a risk factor for liver fibrosis progression in euthyroid individuals. These findings uncover a potential molecular link between thyroid hormone signaling and the development of liver fibrosis, warranting further investigation.
Keywords: thyroid hormone sensitivity; liver fibrosis; uric acid; TFQI; FIB-4